Pengaruh Konseling Kelompok CBT Teknik Biblioterapi untuk Meningkatkan Kemampuan Manajemen Waktu - Purwaningsih, Dwi Afriani; Lianasari, Dewi (Prosiding University Research Colloquium, 2021)
This research aims to examine the effect of CBT group counseling with bibliotherapy techniques to improve students' time management skills. The research was conducted on grade VII students of SMP Negeri 39 Purworejo T.A 2020/2021. This research is a type of pre-experimental research with the research design used is one group pretest-posttest design. The research subjects were selected by purposive sampling. The samples taken were 6 class VII students. The data collection method is done by using a time management capability scale. The data analysis technique used statistical parametric analysis with paired sample ttest with the help of SPSS 24 for Windows. The results of this study indicate that the CBT group counseling with bibliotherapy techniques have an effect on improving students' time management skills, this is evidenced by the results of the paired sample t-test with a probability of Sig. (2-tailed) 0.015 <0.05. The results also showed an increase in the average posttest score of 14.33.